Students' Perception on the Use of Zoom Meeting for Learning Speaking - Khotimah, Khusnul (RETAIN : Journal of Research in English Language Teaching, 2022)
TheoutbreakofCovid-19pandemicforcedmosteducationinstitutionsworldwide to move their teaching and learning online. Zoom Meeting is a learning platform that can be used during the pandemic. The purpose of this study was to describe the use of Zoom Meetings for learning speaking in online class including student perceptions and challenges. Qualitative descriptive research was used to describe students' perceptions about the use of Zoom Meetings in learning speaking. The participants of this research were 34 students of class XI in one of private high school in Gresik. The researcher used observation and semi-structured interview in online and offline to obtain data. The results showed that students gave positive responses that they felt enjoy and motivated in learning speaking using Zoom Meeting. Meanwhile, the students also faced several challenges in using Zoom Meeting during learning which include internet network or access, language capability, and self-confidence